Persepsi Petani pada Program Gerakan Membangun Petani Milenial (Gerbang Tami) di Kecamatan Bulu Kabupaten Sukoharjo - Puspaningtyas, Ermanda; Winarno, Joko; Suminah, Suminah (Jurnal KIRANA, 2024)
The Millennial Farmer Development Movement Program (Gerbang Tami) is a Sukoharjo Regency Government program which aims to encourage the millennial generation to get involved in agricultural activities. The aim of this research is to describe the factors that form perceptions (non-formal education, farmer experience, land area, social environment, economic environment) and farmers' perceptions of the Millennial Farmer Development Movement (Gerbang Tami) program; analyzing the influence of perception-forming factors on farmers' perceptions of the Millennial Farmer Development Movement (Gerbang Tami) program. The research location was determined deliberately, in Bulu District, Sukoharjo Regency. The data analysis method uses multiple linear regression. The sample consisted of 70 respondents and was determined using proportional random sampling technique. The research results show that the factors forming perceptions consisting of non-formal education, farmer experience, social environment are in the good category, while the economic environment is in the less good category. Farmers' perceptions of the Millennial Farmers Development Movement (Gerbang Tami) program are included in the good category. The results of multiple linear regression analysis show that at the Î± = 5% level, farmers' perceptions of the Millennial Farmers Development Movement (Gerbang Tami) program are influenced by the non-formal education variable (sig = 0.000); farmer experience (sig = 0.000), social environment (sig = 0.000), while the variables of land area and economic environment have no significant effect. The independent variables consisting of non-formal education, farmer experience, land area, social environment and economic environment together have an influence on farmer perceptions of 59.3%.